Indications about professional training in Degree in Art (Visuals, Music, Dance, Theater) in the State of Sao Paulo - Moreira, Ana Marcia Akaui; Godoy, Kathya Maria Ayres de [UNESP] (Editora Univ Leopoldlanum, 2024)
This article presents an initial survey of degree courses in Art (Visual, Music, Dance and Theater) in the State of Sao Paulo. This is an excerpt from post-doctoral research hosted by the Institute of Arts in the Universidade Estadual Paulista (IA/UNESP), which reflects on the training of Art teachers. To contribute to this reflection, we bring authors who study human formation in fact that the aspects whitch involve educational, political and social praxis (Freire, 1996; Dardot; Laval, 2016; Novoa, 2023) among others. The first results indicate that, in addition to the decreasing number of Art teachers in their specialties, currently the training of professionals, in general, seems to be turning more towards the capitalist market than the humanist one.
Keywords: Degrees in art; Teacher training; Education